Prioritising fished stocks for monitoring and assessment: A decision analysis approach for diverse fisheries of limited commercial value. (1st January 2021) - Fowler, Ashley M.; Hall, Karina C.; Liggins, Geoffrey W.; Chick, Rowan C.
Abstract: Prioritising fished stocks for monitoring and assessment is a challenge for management of resource-limited fisheries. We developed a participatory multi-criteria decision analysis (MCDA) to prioritise 141 fished stocks in New South Wales (NSW), Australia, based on their importance to fisheries management. The approach aimed to: (1) structure the decision problem, (2) force consideration of management objectives at the stock level, (3) balance trade-offs generated by competing objectives, and (4) balance differences in the perceived importance of objectives among fisheries managers. Performance scores and criteria weightings for ten management objectives were elicited from two groups of managers (commercial and recreational), combined into a total performance value for each stock, and ordered to infer priority for assessment. Stocks with higher total performance values typically had an exploitation status of Overfished, Growth-overfished, or Uncertain and were subject to a catch quota, because these criteria were weighted highly by both management groups. However, total performance was more sensitive to differences in weightings between management groups than to variations in relative magnitude of weightings among criteria. The priority list of stocks will assist decisions regarding the optimal allocation of resources for fisheries research in NSW. This MCDA approach is adaptive and can incorporate changes in management priorities through time and additional ecosystem components. Graphical abstract: Image 1 Highlights: A decision analysis approach was developed to prioritise fished stocks for assessment. Stocks were evaluated according to numerous fishery management objectives. Exploitation status and catch quotas drove stock priorities in the model. Preferences of fisheries managers had a strong impact on stock priorities.